1956. Impact of an Implementation Science-Based Project to Address COVID-19 Vaccine Hesitancy. (15th December 2022) - Ratzan, Scott C; Hultgren, Erin; Carter, Jeffrey D; Rodriguez, Melissa; Simone, Laura; Molloy, Leah
Abstract: Background: COVID-19 vaccine uptake remains suboptimal. This project aimed to identify and mitigate reasons for vaccine hesitancy. Baseline patient knowledge and attitudes about COVID-19 vaccination Methods: Between 9/2021 and 1/2022, 16 live in-person and/or virtual patient education programs were held in community centers/clinics in NC and GA. Surveys were administered before/after each session, and longitudinal outcomes 3 weeks later. Results: Surveys were conducted amongst the 1381 participating patients. 64% were already fully vaccinated against COVID-19, 19% had received 1 of 2 doses, and 17% were either unvaccinated (14%) or unsure of their status (3%). Baseline vaccine knowledge was higher among fully vaccinated patients, with patient attitudes varied per vaccination status (Figure). Patients not planning to get vaccinated cited concern for long-term (21%) and short-term (18%) side effects, thinking the vaccines were developed too quickly (16%), not feeling the vaccine would protect them (10%), and not feeling at risk for serious illness (10%). When asked what they thought would increase patient interest in vaccination, providers (n = 28) identified a strong recommendation (39%) or more information (36%) from a patient's own doctor, while patients prioritized transportation (28%), vaccine availability in their doctor's office (23%), and information from their doctor (23%). Provider confidence in counseling patients improved after the program; more providers felt confident discussing vaccine safety (69%) and efficacy (69%) after the program than at baseline (33% and 41%, respectively). More patients felt confident sharing COVID-19 vaccine information with family and friends after the program (73%) than before (53%). Gains in patient views about COVID-19 vaccination were greatest among those who were unvaccinated/unsure; among this group, more patients agreed that vaccines are safe (72%), effective (76%), and important (78%) after the education, compared to 42%, 46%, and 52% at baseline, respectively. In the longitudinal patient follow-up survey 86% of unvaccinated patients got vaccinated after completing the education session. Conclusion: Patient knowledge and attitudes varied based on vaccine experience, as did patient and provider perceptions about improving vaccine acceptance. Vaccine uptake was high following the program. Disclosures: Scott C. Ratzan, MD, MPA, Abbvie: Stocks/Bonds|Astra Zeneca: Stocks/Bonds|baxter: Stocks/Bonds|Bristol Myers Squibb: Stocks/Bonds|Merck: Grant/Research Support|Quest Diagnostics: Stocks/Bonds|United Health Group: Stocks/Bonds|Usana Health. Services: Stocks/Bonds|vertex: Stocks/Bonds.